THE EFFECT OF CAREER DEVELOPMENT, CULTURE VALUE AND EMOTIONAL INTELLIGANCE ON PERSONAL BRANDING WITH SELF-EFFICACY AS A VARIABLE MEDIATION IN STATE CIVIL APPARATUS (ASN) IN THE GOVERNMENT OF TEGAL CITY - Dean Hadi Pratama; Corry Yohana; Widya Parimita (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the influence of Career Development, Culture Value, and Emotional Intelligence on Personal Branding with Self-Efficacy as a mediating variable in State Civil Apparatus (ASN) in Tegal City Government. The study used a quantitative approach with a survey method by distributing questionnaires to 360 ASN consisting of Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). The sampling technique used proportionate stratified random sampling, while data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4. The results showed that Career Development, Culture Value, and Emotional Intelligence had a positive and significant effect on Self-Efficacy. In addition, these three variables also have a positive and significant effect on Personal Branding. Self-Efficacy was proven to have a positive and significant effect on Personal Branding and was able to significantly mediate the influence of Career Development, Culture Value, and Emotional Intelligence on Personal Branding. The coefficient of determination value shows that the model is able to explain 70.1% of the variation in Self-Efficacy and 76.8% of the variation in Personal Branding. The findings of this study indicate that strengthening the career development system, internalizing organizational cultural values, and increasing emotional intelligence can increase the self-confidence of ASN which ultimately strengthens Personal Branding in carrying out tasks and public services. This study provides an empirical contribution to the development of public sector human resource management, particularly in efforts to improve the professionalism and image of the apparatus through strengthening internal organizational factors.